ECO-FRIENDLY TRANSPORTATION: SOLAR CAR DESIGN FOR COMPETITION- PART I, STRUCTURAL CHASSIS - Behzad Hamedi; Kiran Marques; Ryan Vargo; Hanshin Lee; Kurt Peng; Eashan Gupta; Saied Taheri (International Journal of Innovations in Engineering Research and Technology, 2023)
The design and analysis of the structural chassis for a solar-powered car are crucial aspects of ensuring driver safety and supporting the vehicle’s mechanical and electrical systems. This paper is the first part of a four-part series that covers the design and development of an eco-friendly solar car for competition. The project is divided into multiple parts to provide further details of each aspect. Part I focuses on the design and analysis of the chassis, with an emphasis on achieving driver safety and a lightweight architecture. In this paper, we present the design methodology employed by the Virginia Tech Solar Car Project team during the 2022-2023 timeframe. The design process involves conducting multiple static and dynamic clearance analyses to ensure sufficient space among the chassis and other dynamic systems while maintaining optimal driver positioning. Additionally, impact and stress analyses are performed to assess the chassis’ strength and identify areas for structural enhancements.The results of the analysis demonstrate that the designed chassis meets the required safety standards as well as performance criteria. The design approach prioritizes lightweight construction without compromising the structural integrity of the chassis. Throughout the design process, various challenges are encountered, which will be discussed in detail to provide holistic insights and lessons learned.